AB0191 DECREASING DELAY TO DIAGNOSIS AND TREATMENT OF RHEUMATOID ARTHRITIS: STILL DIFFICULT TO TREAT WITHIN THE WINDOW OF OPPORTUNITY. (2nd June 2020) - Albuquerque, C.; Gomides, A. P.; Vargas-Santos, A. B.; Brenol, C.; Pereira, I.; Bonfiglioli, K.; Bertolo, M.; Guimarães, M. F.; Sauma, M.; Louzada, P.; Giorgi, R.; Radominsky, S.; et al.
Abstract : Background: The need for early rheumatoid arthritis (RA) treatment for better outcomes is widely accepted. Is that goal being achieved in real-life settings? Objectives: To evaluate changes in the delay to RA diagnosis and treatment, and in the proportions of patients being treated early along the last decades in Brazil. Methods: This study was drawn from the REAL cohort, designed to assess RA management under real-life conditions. Patients ≥ 18 years old attending public hospitals in Brazil and meeting RA classification criteria were included. Subjects were stratified according to the year their symptoms began. Delays from symptoms onset to RA diagnosis and treatment were inquired. Early RA diagnosis and treatment was assessed using three different cut points: ≤3, ≤6 and ≤12 months of symptoms onset. Mann-Kendall's trend test, chi-square tests, Welch's ANOVA and Games-Howell's post-hoc tests were used to test hypotheses, at 0.05 significance level. Results: 1116 RA patients were included; 89.4% female; 56.8% white; mean (SD) age 57.1 (11.5) years. A downward trend was found in the delay to RA diagnosis (tau = -0.677, p < 0.001) and treatment (tau = -0.695, p < 0.001) from 1990 to 2015 (Figures 1 and 2 ). The year of symptoms onset was associated with the frequency of early treatment for all defined cut points: ≤3 months (χ 2 = 11.25, p = 0.001), ≤6 months (χ 2 = 34.84, p < 0.001), and ≤12 months (χ 2 = 64.79, p<0.001). The more recent the year of symptoms onset, the higher the proportions of individuals treated early (Table 1 ). Groups stratified according to successive periods of symptoms onset differed in the mean delay to RA treatment [F(5, 372.8) = 41.9; p < 0.001]. Patients with symptoms initiated more recently (2011-2015) had significantly lower delays compared to all other groups. Nonetheless, only 36.3% of these patients with more recent disease started treatment within 6 months of symptoms onset, and 17.2% within 3 months. Conclusion: Delays to RA diagnosis and treatment have decreased, and more patients have been treated within defined windows for early RA management in the last decades in Brazil. Despite all improvements, it was still difficult to attain early RA treatment. Additional efforts are warranted in pursuit of that goal. Disclosure of Interests: Cleandro Albuquerque Grant/research support from: Has received personal fees and/or non-financial support from Pfizer, AbbVie, AstraZeneca, Janssen, Bristol-Myers Squibb, Roche, Novartis and UCB, Consultant of: Has received personal fees and/or non-financial support from Pfizer, AbbVie, AstraZeneca, Janssen, Bristol-Myers Squibb, Roche, Novartis and UCB, Paid instructor for: Has received personal fees and/or non-financial support from Pfizer, AbbVie, AstraZeneca, Janssen, Bristol-Myers Squibb, Roche, Novartis and UCB, Speakers bureau: Has received personal fees and/or non-financial support from Pfizer, AbbVie, AstraZeneca, Janssen, Bristol-Myers Squibb, Roche, Novartis and UCB, Ana Paula Gomides Consultant of: Abvvie, Ana Beatriz Vargas-Santos Grant/research support from: Has received supporting for international medical events from AbbVie and Janssen, Claiton Brenol: None declared, Ivanio Pereira Grant/research support from: Has received consulting fees, speaking fees and supporting for internationals congresses from Roche, Pfizer, UCB Pharma, Eli-Lilly, Abbvie and Janssen, Consultant of: Has received consulting fees, speaking fees and supporting for internationals congresses from Roche, Pfizer, UCB Pharma, Eli-Lilly, Abbvie and Janssen, Paid instructor for: Has received consulting fees, speaking fees and supporting for internationals congresses from Roche, Pfizer, UCB Pharma, Eli-Lilly, Abbvie and Janssen, Speakers bureau: Has received consulting fees, speaking fees and supporting for internationals congresses from Roche, Pfizer, UCB Pharma, Eli-Lilly, Abbvie and Janssen, Karina Bonfiglioli Consultant of: Roche, Abbvie, Pfizer, Janssen and BMS, Manoel Bertolo Grant/research support from: Has participated in clinical and/or experimental studies related to this work and sponsored by Roche; has delivered speeches at events related to this work and sponsored by AbbVie and Pfizer, Paid instructor for: Has participated in clinical and/or experimental studies related to this work and sponsored by Roche; has delivered speeches at events related to this work and sponsored by AbbVie and Pfizer, Speakers bureau: Has participated in clinical and/or experimental studies related to this work and sponsored by Roche; has delivered speeches at events related to this work and sponsored by AbbVie and Pfizer, Maria Fernanda Guimarães: None declared, Maria Sauma: None declared, Paulo Louzada Jr Grant/research support from: Has received supporting for internationals congresses from Bristol-Myers Squibb, UCB and consulting fees from Pfizer, Paid instructor for: Has received supporting for internationals congresses from Bristol-Myers Squibb, UCB and consulting fees from Pfizer, Speakers bureau: Has received supporting for internationals congresses from Bristol-Myers Squibb, UCB and consulting fees from Pfizer, Rina Giorgi Grant/research support from: Has received consulting fees, speaking fees and supporting for internationals congresses from Roche, Pfizer, Bristol-Myers Squibb, UCB, Eli-Lilly, AbbVie, Abbott and EMS, Consultant of: Has received consulting fees, speaking fees and supporting for internationals congresses from Roche, Pfizer, Bristol-Myers Squibb, UCB, Eli-Lilly, AbbVie, Abbott and EMS, Paid instructor for: Has received consulting fees, speaking fees and supporting for internationals congresses from Roche, Pfizer, Bristol-Myers Squibb, UCB, Eli-Lilly, AbbVie, Abbott and EMS, Speakers bureau: Has received consulting fees, speaking fees and supporting for internationals congresses from Roche, Pfizer, Bristol-Myers Squibb, UCB, Eli-Lilly, AbbVie, Abbott and EMS, Sebastião Radominsky Grant/research support from: Has received consulting and speaking fees from Abbvie, Janssen, Pfizer, Roche and UCB, Consultant of: Has received consulting and speaking fees from Abbvie, Janssen, Pfizer, Roche and UCB, Paid instructor for: Has received consulting and speaking fees from Abbvie, Janssen, Pfizer, Roche and UCB, Speakers bureau: Has received consulting and speaking fees from Abbvie, Janssen, Pfizer, Roche and UCB, Licia Mota Grant/research support from: Has received personal or institutional support from AbbVie, Janssen, Pfizer and Roche; has delivered speeches at events related to this work and sponsored by AbbVie, Janssen, Pfizer, Roche and UCB., Speakers bureau: Has received personal or institutional support from AbbVie, Janssen, Pfizer and Roche; has delivered speeches at events related to this work and sponsored by AbbVie, Janssen, Pfizer, Roche and UCB., Geraldo Castelar Grant/research support from:: Has received consulting fees from AbbVie, Bristol-Myers Squibb, Eli Lilly, Glaxosmithkline, Janssen, Pfizer, Sanofi Genzyme and Roche, Consultant of:: Has received consulting fees from AbbVie, Bristol-Myers Squibb, Eli Lilly, Glaxosmithkline, Janssen, Pfizer, Sanofi Genzyme and Roche, Paid instructor for:: Has received consulting fees from AbbVie, Bristol-Myers Squibb, Eli Lilly, Glaxosmithkline, Janssen, Pfizer, Sanofi Genzyme and Roche, Speakers bureau:: Has received consulting fees from AbbVie, Bristol-Myers Squibb, Eli Lilly, Glaxosmithkline, Janssen, Pfizer, Sanofi Genzyme and Roche